A new species of Perlesta (Plecoptera: Perlidae) from North Carolina with additional records for North Carolina and Virginia - Kondratieff, Boris C. (Illiesia, 2011)
The male of Perlesta beatyi n. sp. is described from Robeson County, North Carolina, U.S.A. and is distinguished by truncate paraproct apices with a small obscure tooth. New species records for Perlesta of North Carolina and Virginia are also given with comments on the distribution of the species in this area.
Keywords: entomologija; entomology; nove vrste; Plecoptera; Perlidae; Perlesta; new species; new records; USA; North Carolina; Virginia